2016
DOI: 10.1088/0953-2048/29/11/113004
|View full text |Cite
|
Sign up to set email alerts
|

The development of MgB2superconducting wires fabricated with an internal Mg diffusion (IMD) process

Abstract: In this review, we introduce the development of internal Mg diffusion (IMD)-processed MgB2 superconducting wires. First, a brief history of the IMD method (which has been given different names by different groups) is introduced and the mechanism of IMD MgB2 wire is discussed. Second, factors related to Jc and Je including: boron (B) powder and carbon (C) addition, the ‘effective MgB2 density’ (the MgB2 layer excluding pores, unreacted B particles, MgO, and other impurities), grain size, flux pinning, and conne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 42 publications
(26 citation statements)
references
References 80 publications
0
26
0
Order By: Relevance
“…1(a) shows the magnetic field dependence of the transport critical current density Jc at 4.2 K of Ba-122 tapes in this work and the properties of other type of superconducting wires or tapes are also included. [26][27][28][29] The transport Jc at 4.2 K in this work reaches 1.5  10 5 A/cm 2 (Ic = 437 A) at 10 T and 5.5  10 4 A/cm 2 at 27 T, respectively. These Jc values are the highest values not only for the Ba-122 tapes but 6 also for all of the iron-based superconducting wires and tapes ever reported.…”
Section: Resultsmentioning
confidence: 83%
“…1(a) shows the magnetic field dependence of the transport critical current density Jc at 4.2 K of Ba-122 tapes in this work and the properties of other type of superconducting wires or tapes are also included. [26][27][28][29] The transport Jc at 4.2 K in this work reaches 1.5  10 5 A/cm 2 (Ic = 437 A) at 10 T and 5.5  10 4 A/cm 2 at 27 T, respectively. These Jc values are the highest values not only for the Ba-122 tapes but 6 also for all of the iron-based superconducting wires and tapes ever reported.…”
Section: Resultsmentioning
confidence: 83%
“…After the assembly is cold deformed into wires, the Mg melts and diffuses into the surrounding B powder to form the MgB 2 superconducting phase during the final heat treatment. Compared with the commercialized PIT process, the IMD process is easy to obtain high-density MgB 2 phase, thus achieving high transport J c , so it has been the hotspot for the research of MgB 2 wires ( Ye and Kumakura, 2016 ).…”
Section: Materials Challenges and Current State Of Practical Applicationsmentioning
confidence: 99%
“…At present, 100-meter-class MgB 2 wires based on IMD method have been achieved in several labs ( Ye and Kumakura, 2016 ; Wang et al, 2016 ), while companies such as Hyper Tech in the USA, Columbus in Italy, Hitachi in Japan, Sam Dong in South Korea, and Western Superconducting Technologies in China have possessed a production capacity of kilometer-level practical MgB 2 wires ( J c = 1-2×10 5 A/cm 2 at 4.2 K and 4 T) based on the PIT method. Among them, the MgB 2 wires produced by Hyper Tech and Columbus have been successfully employed in applications such as MRI, superconducting fault current limiter, and superconducting cables.…”
Section: Materials Challenges and Current State Of Practical Applicationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Our group recently developed a novel method for producing uniform nanometer-scale CCs on amorphous boron powder, when we initially attempted to prepare a uniform dispersion for the carbon doping of MgB 2 superconducting wires. , This technique involves the direct pyrolysis of coronene (C 24 H 12 ), a polycyclic aromatic hydrocarbon comprising six peri-fused benzene rings with a high carbon content of 96%. Transmission electron microscopy (TEM) observation revealed that all boron particles were uniformly coated with carbon to a thickness of several nanometers .…”
Section: Introductionmentioning
confidence: 99%